The effects of acetylcholinesterase inhibitors on the heart in acute myocardial infarction and heart failure: From cells to patient reports - Thawatchai Khuanjing (2020)
© 2019 Scandinavian Physiological Society. Published by John Wiley & Sons Ltd Cardiovascular diseases remain a major cause of morbidity and mortality worldwide. Cardiovascular diseases such as acute myocardial infarction, ischaemia/reperfusion injury and heart failure are associated with cardiac autonomic imbalance characterized by sympathetic overactivity and parasympathetic withdrawal from the heart. Increased parasympathetic activity by electrical vagal nerve stimulation has been shown to provide beneficial effects in the case of cardiovascular diseases in both animals and patients by improving autonomic function, cardiac remodelling and mitochondrial function. However, clinical limitations for electrical vagal nerve stimulation exist because of its invasive nature, costly equipment and limited clinical validation. Therefore, novel therapeutic approaches which moderate parasympathetic activities could be beneficial for in the case of cardiovascular disease. Acetylcholinesterase inhibitors inhibit acetylcholinesterase and hence increase cholinergic transmission. Recent studies have reported that acetylcholinesterase inhibitors improve autonomic function and cardiac function in cardiovascular disease models. Despite its potential clinical benefits for cardiovascular disease patients, the role of acetylcholinesterase inhibitors in acute myocardial infarction and heart failure remediation remains unclear. This article comprehensively reviews the effects of acetylcholinesterase inhibitors on the heart in acute myocardial infarction and heart failure scenarios from in vitro and in vivo studies to clinical reports. The mechanisms involved are also discussed in this review.